ANALYSIS OF MATHEMATICAL CONNECTION ABILITY IN SOLVING HOTS QUESTIONS ON ARITHMETIC SEQUENCE - Sukmayanti, Sukmayanti; Karniman, Tegoeh S.; Rizal, Muh; Hasbi, Muh (JME (Journal of Mathematics Education), 2023)
Mathematical connection ability needs to be analyzed so that teachers can get an overview of students' mathematical connection abilities and develop learning strategies to improve students' mathematical connection abilities. This study explores the mathematical connection abilities of class XI MAN 2 Kota Palu students in solving HOTS arithmetic sequence problems. The type of research is qualitative and uses student interview results as data. The results of this research show that mathematical connections high-ability students demonstrate strong connections between arithmetic series and algebra, exponents, and roots, and apply these concepts in real-life and economic contexts. Moderately skilled students link arithmetic sequences to algebra but struggle with economic connections. Low-ability students face challenges linking mathematical concepts, applying arithmetic series to daily life, and connecting it with economics. Understanding these abilities helps teachers tailor strategies to enhance students' mathematical connections, aiding their problem-solving skills.